Oral frailty and its influencing factors in patients with cancer undergoing chemotherapy: a cross-sectional study - Fangyi Li; Tian Xiao; Xueqin Qiu; Chunmei Liu; Qiumei Ma; Dongmei Yu; Linyu Zhou; Ruihan Xiao; Biao He; Ao Tang; Xiaoju Chen (BMC Oral Health)
Abstract Background Oral frailty is one of the easily overlooked complications in patients with cancer, which is as important as dietary dysfunction, malnutrition and other complications. However, limited research exists on the factors influencing oral frailty in patients with cancer undergoing chemotherapy. The objective of this study is to investigate the incidence of oral frailty in patients with cancer undergoing chemotherapy and to analyze the factors that influence it. Methods A convenience sampling method was used to select patients with cancer undergoing chemotherapy from three tertiary hospitals in Chengdu, Sichuan Province. The Oral Frailty Index-8 (OFI-8) was utilized to assess the patients’ oral frailty status. The Chemotherapy-induced Taste Alteration Scale(CiTAS), the Acceptance of Illness Scale(AIS), and the Family Adaptation, Partnership, Growth, Affection, Resolve Index(APGAR) were used to assess the patients’ taste changes, levels of acceptance of illness, and family functioning levels, respectively. Additionally, descriptive analysis, univariate analysis, and multiple linear stepwise regression analysis were conducted. Results The incidence of oral frailty among patients with cancer undergoing chemotherapy was found to be 57.58%. Additionally, oral frailty was positively correlated with chemotherapy-induced taste alteration, while it was negatively correlated with acceptance of illness and family functioning. Furthermore, multiple linear stepwise regression analysis revealed that factors such as disease duration, history of radiation therapy, dry mouth, dentures, chemotherapy-induced taste alteration, acceptance of illness, and family functioning significantly influenced oral frailty in these patients, accounting for a total variance of 54.6%. Conclusion The incidence of oral frailty is notably high among patients with cancer undergoing chemotherapy. Several factors, such as disease duration, history of radiation therapy, dry mouth, the use of dentures, chemotherapy-induced taste alteration, acceptance of illness, and family functioning, significantly affect the degree of oral frailty. This highlights the necessity for healthcare providers to implement preventive management strategies based on these factors, and to modify oral care plans accordingly to prevent or mitigate the onset and progression of oral frailty in patients with cancer undergoing chemotherapy.